Correlation and Evaluation of the Preoperative Computed Tomography with Preoperative Surgical Findings in Patients with Unsafe Chronic Supppurative Otitis Media - Shukla, Navin; Sharma, Varuni; Giri, Rakesh Kumar (Asian Journal of Medical Radiological Research, 2019)
Background: Chronic Suppurative Otitis Media (CSOM) is one of the most common causes of preventable hearing loss especially in developing countries. It is described as a condition of the middle ear that is characterized by persistent or recurrent discharge for three months or more through a perforation of the tympanic membrane. The aim and objective of the study is to correlate and compare preoperated computed tomography with preoperative surgical findings with unsafe chronic suppurative otitis media. Subjects and Methods: A prospective, analytical study was conducted among 90 patients with complaint of unsafe chronic suppurative otitis media which were randomly selected from outpatient Department of ENT at Shridev Suman Subharti Medical College, Dehradun, Uttarakhand. The patients comprised of both males as well as females and also of different age groups. Results: Among 90 study subjects, 32 (35.55%) cases had conductive hearing loss, 11(12.22%) cases had sensorineural type, 40(44.44%) had mixed type and 7(7.77%) had no response. On comparing the per operative findings with those of computed tomography, soft tissue mass in middle ear and mastoid was seen in 87 cases (96.66%) per operatively whereas on computed tomography, it was observed in 80 cases (88.88%). Mastoid air cells were found sclerosed in 72 cases (80%) both per operatively and on computed tomography. Conclusion: In conclusion, the present study pointed that high resolution computed tomography scanning is a modality which can accurately image the pathological anatomy in unsafe chronic suppurative otitis media and represents a major advance in the diagnostic imaging of this disease.